Influence of Ectopic Beats on the Average, Maximum, and Minimum Heart Rates - A. Ajwad, Asmaa; Kadhim Rashid, Muayad; Tariq Ibrahim, Ibrahim; AbdulKareem Salman, Mustafa; Mousa Jaafar, Ali (Diyala Journal of Medicine, 2023)
Background: Heart rate metrics including the average heart rate, maximum heart rate, and minimum heart rate reflect the physiological condition of the heart. Clinically, determining the impact of ventricular and atrial ectopic beats on those three metrics is important because they indicate how hard the heart is working. Objective: To investigate the changes in heart rates of ventricular and atrial ectopic patients. Patients and Methods: In this study, data from 90 persons (30 with ventricular ectopic beats, 30 with atrial ectopic beats, and 30 healthy people) were gathered and analyzed to see what changes in heart rate metrics may occur in patients with ectopic beats. Results: According to our results, the three heart rate metrics in almost all three groups are statistically insignificant (p-value > 0.05). The average heart rate was significantly higher (p<0.05) in ventricular ectopic patients than in atrial ectopic patients. The effect of age and gender on heart rate metrics were statistically assessed. Conclusion: Despite the fact that no significant differences were found in all groups, there were certain differences that require further examination. One of the long-term objectives is to expand this study to incorporate electrocardiography (ECG) analysis in order to complete the comparison between the three groups.